Prevalence of Listeria Monocytogenes in Raw Milk of the Healthy Cattle in Lorestan Province (Iran) by PCR - Amir Mohamad Ebadifar; Amin Jaydari; Nemat Shams; Heidar Rahimi (Fasa University of Medical Sciences, 2022)
Background & Objective: The prevalence of Listeria monocytogenes (L. monocytogene) in milk and dairy products, the high complications and damage associated with zoonotic Listeriosis have led to this bacterium being considered as a risky infection for public health. Materials & Methods: In the present descriptive and cross-sectional study, to investigate the prevalence of L. monocytogene, 100 samples of raw milk obtained from industrial farms in Lorestan province in winter and spring of 2019-2020 were collected and 16SrRNA and hlyA genes were detected using PCR reaction to identify Listeria genus and L. monocytogene species, respectively. Results: Based on the observed results, three samples (3%) were positive for Listeria genus, while no report of L. monocytogens species was observed. Conclusion: The results of this study did not show evidence of the presence of L. monocytogenes in raw cow milk, which indicates the sanitation and desirable nutritional conditions in industrial farms. Therefore, due to the presence of Listeria (other species of Listeria) in raw milk, if you consume raw and unpasteurized milk, the risk of human infection with listeriosis should not be ignored.